ANALYSIS OF OUTPATIENT SERVICE WAITING TIME IN THE JKN ERA AT X HOSPITAL PEKANBARU - Dewi, Nur Husna; Hartono, Budi; Nofiyadi, Nofiyadi (HEARTY, 2026)
The implementation of National Health Insurance (JKN) requires hospitals to provide fast and high-quality services to ensure patient satisfaction. However, outpatient services still face problems such as patient waiting times that exceed standards, indicating inefficiency in service flow and management. This condition has the potential to reduce service quality and the satisfaction of JKN participants. This study aims to determine and describe the waiting time for outpatient services in the JKN era at X Hospital Pekanbaru. This study uses a qualitative descriptive design with observation, interview, and document review techniques. Informants were selected purposively, and data analysis was conducted through triangulation and a problem-solving cycle including USG and fishbone analysis methods. The results indicate several problems in outpatient services at X Hospital Pekanbaru, namely long patient waiting times during registration, doctor examinations, and medication services, limited outpatient and registration staff, obstacles to online JKN registration, ineffective staff communication, and limited waiting room facilities. Problem prioritization using the USG method revealed that long service waiting times are the main problem because they directly impact service quality and patient satisfaction, influenced by limited human resources and inefficient service flows. Observation results showed that average patient waiting time reached 104.1 minutes, with 61.8% of patients waiting more than 60 minutes and only 17.5% being served according to ideal waiting time standards. The problem of long waiting times indicates that the quality of outpatient services at X Hospital Pekanbaru is not yet optimal and requires system improvements.